Вегетативне розмноження Dianthus hypanicus Andrz. в умовах культури у Правобережному Лісостепу України - Goncharuk, L.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The results of Dianthus hypanicus Andrz. vegetative propagation in conditions of culture in the Right-Bank of Forest-Steppe of Ukraine are presented. Different terms of rooting are studied; a number of substrata are tested. It is established that the optimal method of D. hypanicus vegetative propagation is a cutting in conditions of protected ground in moistened sand with use of growth-promoting factor and cuttings prepared in early terms (May – June).